Tsg101 positively regulates physiologic‐like cardiac hypertrophy through FIP3‐mediated endosomal recycling of IGF‐1R. Issue 6 (18th March 2019) - Essandoh, Kobina; Deng, Shan; Wang, Xiaohong; Jiang, Min; Mu, Xingjiang; Peng, Jiangtong; Li, Yutian; Peng, Tianqing; Wagner, Kay-Uwe; Rubinstein, Jack; Fan, Guo-Chang
ABSTRACT: Development of physiologic cardiac hypertrophy has primarily been ascribed to the IGF‐1 and its receptor, IGF‐1 receptor (IGF‐1R), and subsequent activation of the protein kinase B (Akt) pathway. However, regulation of endosome‐mediated recycling and degradation of IGF‐1R during physiologic hypertrophy has not been investigated. In a physiologic hypertrophy model of treadmill‐exercised mice, we observed that levels of tumor susceptibility gene 101 (Tsg101), a key member of the endosomal sorting complex required for transport, were dramatically elevated in the heart compared with sedentary controls. To determine the role of Tsg101 on physiologic hypertrophy, we generated a transgenic (TG) mouse model with cardiac‐specific overexpression of Tsg101. These TG mice exhibited a physiologic‐like cardiac hypertrophy phenotype at 8 wk evidenced by: 1 ) the absence of cardiac fibrosis, 2 ) significant improvement of cardiac function, and 3 ) increased total and plasma membrane levels of IGF‐1R and increased phosphorylation of Akt. Mechanistically, we identified that Tsg101 interacted with family‐interacting protein 3 (FIP3) and IGF‐1R, thereby stabilizing FIP3 and enhancing recycling of IGF‐1R. In vitro, adenovirus‐mediated overexpression of Tsg101 in neonatal rat cardiomyocytes resulted in cell hypertrophy, which was blocked by addition of monensin, an inhibitor of endosome‐mediated recycling, and by small interfering RNA—mediated knockdown (KD) of FIP3. Furthermore, cardiac‐specific KD of Tsg101 showed a significant reduction in levels of endosomal recycling compartment members (Rabila and FIP3), IGF‐1R, and Akt phosphorylation. Most interestingly, Tsg101‐KD mice failed to develop cardiac hypertrophy after intense treadmill training. Taken together, our data identify Tsg101 as a novel positive regulator of physiologic cardiac hypertrophy through facilitating the FIP3‐mediated endosomal recycling of IGF‐1R.—Essandoh, K., Deng, S., Wang, X., Jiang, M., Mu, X., Peng, J., Li, Y., Peng, T., Wagner, K.‐U., Rubinstein, J., Fan, G.‐C. Tsg101 positively regulates physiologic‐like cardiac hypertrophy through FIP3‐mediated endosomal recycling of IGF‐1R. FASEB J. 33, 7451–7466 (2019). www.fasebj.org